Self-assembled plasmonic core-shell clusters with an isotropic magnetic dipole response in the visible range - Mühlig, Stefan; Cunningham, Alastair; Scheeler, Sebastian Paul; Pacholski, Claudia; Bürgi, Thomas; Rockstuhl, Carsten; Lederer, Falk (ACS nano, 2011)
We theoretically analyze, fabricate, and characterize a three-dimensional plasmonic nanostructure that exhibits a strong and isotropic magnetic response in the visible spectral domain. Using two different bottom-up approaches that rely on self-organization and colloidal nanochemistry, we fabricate clusters consisting of dielectric core spheres, which are smaller than the wavelength of the incident radiation and are decorated by a large number of metallic nanospheres. Hence, despite having a complicated inner geometry, such a core-shell particle is sufficiently small to be perceived as an individual object in the far field. The optical properties of such complex plasmonic core-shell particles are discussed for two different core diameters.
Gesehen am14.09.2022